2017
DOI: 10.1371/journal.pone.0171464
|View full text |Cite
|
Sign up to set email alerts
|

Activation of MAPK/ERK signaling by Burkholderia pseudomallei cycle inhibiting factor (Cif)

Abstract: Cycle inhibiting factors (Cifs) are virulence proteins secreted by the type III secretion system of some Gram-negative pathogenic bacteria including Burkholderia pseudomallei. Cif is known to function to deamidate Nedd8, leading to inhibition of Cullin E3 ubiquitin ligases (CRL) and consequently induction of cell cycle arrest. Here we show that Cif can function as a potent activator of MAPK/ERK signaling without significant activation of other signaling pathways downstream of receptor tyrosine kinases. Importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…We found that one additional cellular target of Cif is the ERK MAPK pathway. We have recently shown that activation of ERK by Cif is CRL independent ( Ng et al, 2017 ). However, ERK activation was not involved in the Cif-mediated stimulation of B. thailandensis replication.…”
Section: Discussionmentioning
confidence: 99%
“…We found that one additional cellular target of Cif is the ERK MAPK pathway. We have recently shown that activation of ERK by Cif is CRL independent ( Ng et al, 2017 ). However, ERK activation was not involved in the Cif-mediated stimulation of B. thailandensis replication.…”
Section: Discussionmentioning
confidence: 99%
“…B. pseudomallei TssM, the homologous protein of B. mallei TssM, acts as a DUB, and has been currently identified to inhibit the activation of NF-kB by promoting its substrates TRAF-3, TRAF-6 and IκBα deubiquitination 48 . In addition, CHBP (Cif homolog from B. pseudomallei ) can catalyze the deamidation of Gln 40 in ubiquitin and NEDD8 to inhibit Cullin RING E3 ubiquitin ligases (CRL) activity in vitro 49 , and further be verified to activate MAPK/ERK signaling in cellular assays which is independent of CRL inhibition 50 , 51 . Of note, many pathogenic B. pseudomallei strains lack the Cif gene, suggesting that CHBP is not an essential virulence factor in B. pseudomallei 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Protein ubiquitination also plays crucial roles in controlling eukaryotic cell homeostasis and pathogenesis of neoplastic, infectious, and neurodegenerative diseases [ 51 ]. B. pseudomallei Cif has been shown to modify host central signaling pathways by activating MAPK/ERK signaling to induce the phosphorylation of the pro-apoptotic protein Bim (Bcl-2 interacting mediator of cell death), and potentially leading to a proapototic effect [ 34 ]. Additionally, Cif was shown to increase basal NF-κB activity and stimulate the intracellular replication of the B. thailandensis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The modus operandi of Cif is known to deamidate Nedd8, an ubiquitin-like protein, which causes the inhibition of Cullin E3 ubiquitin ligases (CRL), and consequently induces cell cycle arrest [ 31 , 32 , 33 ]. B. pseudomallei Cif can function as a potent activator of MAPK/ERK signaling and has CRL independent effects to counter the pro-apoptotic effects [ 34 ]. However, whether Cif employs additional roles on host cells that are crucial for bacterial pathogenesis is currently poorly understood.…”
Section: Introductionmentioning
confidence: 99%